2021
DOI: 10.1007/s11926-021-01033-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Joint Form Variation in Sacroiliac Joint Disease: Current Concepts and New Perspectives

Abstract: Purpose of Review The aim of this article is to further the understanding of anatomical variation of the sacroiliac joint (SIJ) within the rheumatological community and point out promising fields of research in the interplay of SIJ anatomy and joint disease. Recent Findings Mechanical strain has long been implicated in onset and progression of axial spondyloarthritis (axSpA). Recent investigations found changes in the pattern of degenerative lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…Currently, mechanical stress is also considered a trigger factor for chronic inflammatory arthropathies, which, in addition to biomechanical influence, can provoke an immune response. 16,18 In an analysis of the influence of atypical forms on the appearance of inflammatory or structural changes, we found an association This study has several limitations, including the monocentric setting and the retrospective design. The assessment of SIJ changes in MRE was limited compared to the evaluation of joint changes revealed in a dedicated MRI sacroiliac joint protocol due to a lack of inclined projections and a large FOV with lower spatial resolution.…”
Section: Ta B L Ementioning
confidence: 76%
See 1 more Smart Citation
“…Currently, mechanical stress is also considered a trigger factor for chronic inflammatory arthropathies, which, in addition to biomechanical influence, can provoke an immune response. 16,18 In an analysis of the influence of atypical forms on the appearance of inflammatory or structural changes, we found an association This study has several limitations, including the monocentric setting and the retrospective design. The assessment of SIJ changes in MRE was limited compared to the evaluation of joint changes revealed in a dedicated MRI sacroiliac joint protocol due to a lack of inclined projections and a large FOV with lower spatial resolution.…”
Section: Ta B L Ementioning
confidence: 76%
“…The influence of mechanical stress on the appearance of subchondral joint changes has been increasingly discussed. [16][17][18][19][20][21] Several experimental and clinical studies also showed the role of mechanical stress even in developing inflammatory joint diseases. [19][20][21] For instance, Thorarensen et al and Zeng et al demonstrated that physical trauma or prolonged repetitive work, which led to mechanical stress, should be considered a risk factor for inflammatory joint disease in psoriatic (OR: 1.32, 95% CI: 1.13-1.54) and rheumatoid (OR: 1.8, 95% CI: 1.6-2.0) arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Darüber hinaus existieren eine Reihe beschriebener Varianten der anatomischen Form des Sakroiliakalgelenks [13]. Am häufigsten werden die folgenden Varianten beschrieben [14]: das akzessorische Gelenk, das eine zusätzliche Gelenkfacette beschreibt, die sich dorsal des eigentlichen Gelenks im Spatium retroartikulare befindet; der ilio sa krale Komplex, auch als intraartikuläre Formvarian-te bezeichnet, der eine Unebenheit oder größere Einkerbung der Gelenkfläche beschreibt; das sichelförmige Ilium, bei der sich die morphologische Beziehung von Ilium und Sakrum umdreht, hin zu einem konvexen Sakrum gegenüber einem konkaven Ilium.…”
Section: Anatomische Geschlechtsunterschiedeunclassified
“… 8 These anatomical distinctions in joint form have been found to be associated with an increased risk of SIJ pain and dysfunction in females. 25 Ziegeler et al 26 reported that, in a cohort of over 800 patients without documented SIJ disease, atypical joint forms were over four times more likely to occur among females, with an almost five times greater risk of radiographic evidence of dorsal osteophytes formation compared to males.…”
Section: Biomechanical and Clinical Correlatesmentioning
confidence: 99%